PEMANFAATAN KARBON SISA HASIL PEMBENTUKAN KRISTAL LIMBAH TULANG IKAN TENGGIRI (SCOMBEROMORUS COMMERSON LACEPEDE) DAN IKAN BELIDA (CHITALA LOPIS) UNTUK MENGADSORPSI ZAT WARNA SINTETIK CONGO RED - Pino Ramadani; Firnanda Zuni Fransiska; Aisyah Adinda Putri; Tiara Maharani; Salsabila Dia Syahputri; Fitri Nur Rahmadani; Wirhanuddin Wirhanuddin; Mukhamad Nurhadi (Jurnal Inovasi Teknik Kimia, 2025)
To date, industrial wastewater treatment efforts have largely relied on conventional methods that are sensitive to environmental changes and less effective in degrading complex dyes such as Congo Red. One promising alternative approach is adsorption using biomass-based activated carbon, including waste derived from fish bones. This study aims to investigate the properties, surface characteristics, and adsorption mechanism of residual carbon obtained from crystal formation processes using waste bones of mackerel and featherback fish for Congo Red removal. The methodology involved carbonization at 500 °C, followed by sulfonation with concentrated H₂SO₄, and adsorption experiments with varying carbon particle size, contact time, and initial Congo Red concentration. The results demonstrate that fish bone waste carbon is highly effective in adsorbing Congo Red, with removal efficiency increasing with contact time and reaching equilibrium within 10 minutes at 99.8%. The optimum particle size was 200 mesh, and the maximum adsorption capacity was observed at Congo Red concentrations below 600 mg L⁻¹. Isotherm analysis revealed that the adsorption process follows the Langmuir model, with a maximum adsorption capacity of 16,666.6 mg g⁻¹. Meanwhile, kinetic data indicated that the adsorption behavior conforms to a pseudo-second-order model, with a rate constant of 666.6 g mg⁻¹ h⁻¹ at 25 °C.